Association/Dissociation of Caveolin-1 and Nitric Oxide Synthase in Preserving Renal Medulla Function during Hemorrhage and Aging - Arreche, Noelia Daniela (2021)
Background: Caveolin-1 is a negative regulator of endothelial nitric oxide synthase (eNOS), as its interaction and binding suppress the activityof eNOS by making caveolin–eNOS complex. The critical role of caveolin-1 and eNOS in the renal medulla during hypovolemic state and aging isunclear.Objective: To investigate changes in the renal medulla the activity and protein levels of the different NOS forms, changes in the abundance ofcaveolin-1 and caveolin-1/eNOS association in response to acute hemorrhage in young and middle-aged rats.Methods: In the present study we determined: i) NOS activity and protein levels of the different NOS isoforms, ii) the abundance of caveolin-1and, iii) caveolin-1/eNOS association during hypovolemic state of young and middle-aged rats in the kidney.Results: We have demonstrated that caveolin-1 is involved in the regulation of renal NOS activity in response to acute hemorrhage and aging.Conclusion: Our data showed that association/dissociation of caveolin-1 and eNOS in renal medulla play a critical role in preserving the renalfunction during hypovolemic state in young and middle-aged rats.